Surface Activity Of Surfactin Recovered And Purified From Fermentation Broth Using A Two-step Ultrafiltration (UF) Process - Mohd Hafez Mohd Isa; A. Richard Frazier; Paula Jauregi (UKM, 2024)
Sains Malaysiana 40(9)(2011): 1043–1048